Optimization Cultivating Character Values that Become Integrity Nation - Imam Tabroni; Islamiyah Nurkholis; Aldi Robiansyah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Rapid technological advances, whether we realize it or not, are slowly making people begin to ignore cultural values and traditions that have been handed down by their ancestors. In a basic paradigm, there are character values that should be imitated such as values, politeness, courtesy, togetherness, independence, and religiosity. The neglect of cultural values gives birth to an individualistic, materialistic, and hedonistic culture. As for the cultivation of a value foundation that has character in each individual, it should be instilled from an early age, which of course requires cooperation from various elements and support from the environment such as family, school and even the community. And the government has a role to build and instill a national character through the cultivation of character education which is applied to character education